The Evaluation of Social and Professional Life Competences of University Students Through Service-Learning - Santos Rego, Miguel A.; Mella Núñez, Ígor; Naval, Concepción; Vázquez Verdera, Victoria (Frontiers in Education, 2021)
The view previously held in the university regarding teaching-learning processes has changed significantly over the past few years. Undoubtedly, in the case of Europe, this change of pedagogical model has gone hand in hand with the creation of the European Higher Education Area (EHEA). Some of the pivotal areas of EHEA are the independent work of the individual student, the social dimension of learning, and the acquiring of skills, which are not reduced to the mere technical and/or subject matter knowledge. Generic competences and the so-called “soft skills” have also become important, given their significant contribution to the students’ academic, personal, social, and professional development. Predictably, within this framework, new methodologies appear, in line with this educational focus on competences; among these new methodologies include service-learning (SL). It basically consists of introducing a community service into the traditional academic and curricular tasks thereby seeking a better relevance and applicability in the learning processes. This article analyzes the way in which SL contributes to the acquisition, by university students, of a certain skill set which is useful for their social and professional life. To this end, we used a quasi-experimental design, which included pretest and posttest assessments based on a total sample of 1,153 students (789 SL students and 364 non-SL students). The used questionnaire evaluates three important components relevant for the purpose of the present article (perception of the university education, social participation and civic-social competences). The conclusion is that students involved in SL not only show a more positive evolution, but also obtain better results after the projects are completed (regarding satisfaction with the training, and social participation). By the same token, not all students included in the experimental group achieve homogeneous results; the differences are according to variables such as gender, the cycle/year they are enrolled in, area of study or whether or not they previously participated in university service activities. Finally, we observe that this methodology is capable of approaching university education in a holistic way by asserting cross-section type learning processes likely to be useful in the transition from the students’ academic to their professional life.